EXPLORING PRE-SENTENCING MEASURES FOR PEDOPHILIC CRIMES IN DELHI-NCR- AN ANALYTICAL APPROACH - Aakanksha Sharma (Chelonian Research Foundation, 2024)
Pedophilic crimes, involving sexual offenses against minors, have been an alarming concern across the globe, particularly in metropolitan regions like Delhi-NCR. The increasing number of such cases demands not only stringent legal frameworks but also effective pre-sentencing measures to ensure the safety and well-being of victims while ensuring just outcomes for offenders. Pre-sentencing measures are critical steps that help in assessing the nature of the crime, the mental state of the accused, and the protection of the victim. These measures play an important role in determining appropriate punishment, rehabilitation, and the risk of reoffending. In the context of Delhi-NCR, pre-sentencing measures for pedophilic crimes include the investigation phase, psychological assessments of the offender, and victim protection protocols. During the investigation, authorities must ensure the victim’s safety through immediate protection orders, child-friendly interview techniques, and legal safeguards against re-victimization. For offenders, psychological evaluations can help in identifying potential mental health issues or underlying disorders, influencing the sentencing approach. Courts often refer to such evaluations to decide whether rehabilitation or imprisonment should be prioritized. Moreover, pre-sentencing measures also involve a careful review of the offender’s criminal history, societal impact, and the severity of the offense. The court may consider rehabilitative programs that focus on therapy and counseling for offenders with pedophilic tendencies to reduce recidivism. In this regard, Delhi-NCR has seen increasing calls for better coordination between law enforcement, mental health professionals, and child protection agencies. Despite these measures, challenges persist, including the need for more specialized resources, longer-term follow-ups with offenders, and a comprehensive legal system that can swiftly handle cases while maintaining victim support. To address these challenges, a multi-disciplinary approach involving law enforcement, social services, and mental health professionals is necessary to ensure that both the protection of victims and the rehabilitation of offenders are achieved efficiently. Effective implementation of these pre-sentencing measures can contribute to reducing the prevalence of pedophilic crimes and ensuring justice for victims.